Does Chronic Inflammation Play a Role in Rheumatic Mitral Valve Restenosis after Percutaneous Transvenous Mitral Commissurotomy? - Butarbutar, Maruli; Soesanto, Amiliana M; Firman, Doni; Ariani, Rina; Alkatiri, Amir Aziz; Wicaksono, Sony Hilal (Jurnal Kardiologi Indonesia, 2025)
In “Does Chronic Inflammation Play a Role in Rheumatic Mitral Valve Restenosis after Percutaneous Transvenous Mitral Commissurotomy?” (Indonesian Journal of Cardiology, 43(3), 101-107. https://doi. org/10.30701/ijc.1398), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1398. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error. DOI of original article: https://doi.org/10.30701/ijc.1398